1999
DOI: 10.1117/12.350225
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and lithographic parameter extraction for the modified resists

Abstract: The modification of the i-line resist structure after spiking with various amount of poly(4-vmylphenol) polymer is characterized by the spectra of ultraviolet visible (UV-VIS) and gel permeation chromatography (GPC). The chemical structure of photoactive compound is found to be unchanged after modification, while slight change in the polymer chain is obserbed. The resist layer coated onto the wafer is characterized by various methods including n&k analyzer, Nanospec, Fourier transform infrared red (FTIR), ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been suggested that a change in solubility of the systems containing NQD compound and novolac resin after the UV light irradiation is responsible for a change of intermolecular hydrogen bonds between the photosensitive component molecules and macromolecules of novolac resin [88,89,91,92]. Previously proposed mechanism should be supplemented by the following hypothesis: decomposition of NQD derivative leads not only to the hydrophilic indene carboxylic acid, but also to destruction of the hydrogen bonds between the NQD derivative and macromolecules of novolac resin.…”
Section: Supramolecular Photochemistry As the Real Ground For The Devmentioning
confidence: 99%
“…It has been suggested that a change in solubility of the systems containing NQD compound and novolac resin after the UV light irradiation is responsible for a change of intermolecular hydrogen bonds between the photosensitive component molecules and macromolecules of novolac resin [88,89,91,92]. Previously proposed mechanism should be supplemented by the following hypothesis: decomposition of NQD derivative leads not only to the hydrophilic indene carboxylic acid, but also to destruction of the hydrogen bonds between the NQD derivative and macromolecules of novolac resin.…”
Section: Supramolecular Photochemistry As the Real Ground For The Devmentioning
confidence: 99%